The early transcriptional and post-transcriptional responses to fluconazole in sensitive and resistant Candida albicans - Irene Stevens; Fitz Gerald Silao; Susanne Huch; Honglian Liu; Kicki Ryman; Adriana Carvajal-Jimenez; Per O. Ljungdahl; Vicent Pelechano (Scientific Reports)
Abstract Candida albicans is a leading cause of fungal infections in immunocompromised patients. Management of candidemia relies on a few antifungal agents, with fluconazole being first line therapy. The emergence of fluconazole-resistant strains highlights the pressing need to improve our molecular understanding of the drug response mechanisms. By sequencing the 5’P mRNA degradation intermediates, we establish that co-translational mRNA decay occurs in C. albicans and characterize how in vivo 5´-3´ exonuclease degradation trails the last translating ribosome. Thus, the study of the 5’ Phosphorylated mRNA degradome (5PSeq) offers a simple and affordable way to measure ribosome dynamics and identify codon specific ribosome stalls in response to drugs and amino acid deprivation. Building upon this, we combine RNA-Seq and 5PSeq to study the early response of sensitive and resistant C. albicans isolates to fluconazole. Our results highlight that transcriptional responses, rather than changes in ribosome dynamics, are the main driver of Candida resistance to fluconazole.